A Small Molecule That Switches a Ubiquitin Ligase from a Processive to a Distributive Enzymatic Mechanism - Kathman, Stefan G.; Span, Ingrid; Smith, Aaron T.; Xu, Ziyang; Zhan, Jennifer; Rosenzweig, Amy C.; Statsyuk, Alexander V. (Journal of the American Chemical Society, 2015)
E3 ligases are genetically implicated in many human diseases, yet E3 enzyme mechanisms are not fully understood, and there is a strong need for pharmacological probes of E3s. We report the discovery that the HECT E3 Nedd4-1 is a processive enzyme and that disruption of its processivity by biochemical mutations or small molecules switches Nedd4-1 from a processive to a distributive mechanism of polyubiquitin chain synthesis. Furthermore, we discovered and structurally characterized the first covalent inhibitor of Nedd4-1, which switches Nedd4-1 from a processive to a distributive mechanism. To visualize the binding mode of the Nedd4-1 inhibitor, we used X-ray crystallography and solved the first structure of a Nedd4-1 family ligase bound to an inhibitor. Importantly, our study shows that processive Nedd4-1, but not the distributive Nedd4-1:inhibitor complex, is able to synthesize polyubiquitin chains on the substrate in the presence of the deubiquitinating enzyme USP8. Therefore, inhibition of E3 ligase processivity is a viable strategy to design E3 inhibitors. Our study provides fundamental insights into the HECT E3 mechanism and uncovers a novel class of HECT E3 inhibitors.
CRIS-Team Scopus Importer:2021-09-24